Tinjauan Sistematis tentang Collaborative Learning pada Bidang Kimia - Afrahamiryano, Afrahamiryano; Dasna, I Wayan; Habiddin, Habiddin (Edukimia, 2022)
Collaborative Learning (CL) is a learning model that implies cooperation in a group consisting of two or more people to achieve a common goal while respecting each individuals contribution as a whole. CL is more synonymous with social interaction. In the learning process, the centre of attention is the interaction of educators with students, interactions between students, and interactions of students with their environment. The purpose of this review is to look at global trends related to CL research in the field of Chemistry Education. Obtained 62,555 articles discussing CL with various keywords, 88 of which are relevant to the purpose of this article review. After being mapped, there are five research themes related to CL, namely (1) CL based on student activities and the role of educators, (2) Collaboration Strategy for STEM, (3) CL based game, (4) Computer-supported collaborative learning (CSCL), and (5) CL in Laboratory Work. Based on the review findings, research related to CL has excellent potential to be continued and developed, such as collaboration with STEM, games, practicum in the laboratory, and CSCL.